Pastorate in crisis: pastors, heresy, and heretics in Geoffrey of Auxerre’s Sermons on the Apocalypse - Noutsou, Matina (Mos Historicus: A Critical Review of European History, 2025)
The birth of heresy in the 12th century has been related to the overall socio-economic and religious developments of the time. Allegations of heresy could be deployed for political reasons, or they could be expression of a religious antagonism among newly established monastic orders and lay groups and clerics. In this framework, I will discuss the Sermons on the Apocalypse of the Cistercian abbot Geoffrey of Auxerre and particularly the entanglement of heresy allegation and criticism against clergy. The aim is to discover new insights on the Cistercian abbot’s approach towards clergy, and the multiple ways that charges of heresy could be deployed by Geoffrey in order to construct a specific clerical identity in accordance with his monastic thinking and the ideal of spiritual reform.